Flexible watershed simulation with the Raven hydrological modelling framework. (July 2020) - Craig, James R.; Brown, Genevieve; Chlumsky, Robert; Jenkinson, R. Wayne; Jost, Georg; Lee, Konhee; Mai, Juliane; Serrer, Martin; Sgro, Nicholas; Shafii, Mahyar; Snowdon, Andrew P.; Tolson, Bryan A.
Abstract: A general formulation of a surface water hydrological model is posed that enables multiple numerical schemes, model structures, discretization schemes, and interpolation approaches to be tested, compared, and/or used for assessment of structural uncertainty and algorithm skill. This formulation is the basis for the object-oriented and open source hydrological modelling framework Raven. Raven is uniquely capable of fully emulating and then modifying or extending a number of existing hydrological models of differing design, including the UBC watershed model, GR4J, MOHYSE, HMETS, and HBV-EC. More than 100 compatible process algorithm options and more than 80 interchangeable options for both routing and the estimation of forcings support the testing of trillions of possible model configurations. It supports general spatial discretization, including grids, subbasin/hydrologic response units, lumped, or triangulated irregular network models. Raven's utility for examining the impact of model choices and sensitivity to structural model uncertainty is demonstrated with a set of simple test cases. Graphical abstract: Highlights: Flexible hydrologic modelling framework, Raven, introduced. Raven is unique generalized formulation of semi-distributed hydrologic model. Raven supports assessment of wide range of model choices.